2004
DOI: 10.1002/bmc.370
|View full text |Cite
|
Sign up to set email alerts
|

Determination of quercetin in human plasma after ingestion of commercial canned green tea by semi‐micro HPLC with electrochemical detection

Abstract: Determination of quercetin in human plasma was carried out by semi-micro high-performance liquid chromatography with electrochemical detection. Peak heights for quercetin were found to be linearly related to the amount of each quercetin injected from 1.5 to 750 pg. The detection limit (signal-noise ratio, S/N = 3) of the present method for quercetin was 0.3 pg. Glucuronic and sulfate forms of quercetin in plasma were hydrolyzed enzymatically using beta-glucuronidase and sulfatase, respectively. Quercetin in pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 23 publications
1
21
1
1
Order By: Relevance
“…Analytical methods have included LC/MS [4,5], LC/MS/MS [6][7][8], HPLC with UV detection [9], HPLC with fluorescent detection [10], HPLC with electrochemical detection [7,[10][11][12][13][14] and HPLC-radiocounting and tandem mass spectrometry [11]. Following onion ingestion, Witting et al [6] attempted to analyze unchanged quercetin, but were only able to detect quercetin conjugates while Mullen et al [7] reported trace levels of unchanged quercetin in one subject.…”
Section: Introductionmentioning
confidence: 97%
“…Analytical methods have included LC/MS [4,5], LC/MS/MS [6][7][8], HPLC with UV detection [9], HPLC with fluorescent detection [10], HPLC with electrochemical detection [7,[10][11][12][13][14] and HPLC-radiocounting and tandem mass spectrometry [11]. Following onion ingestion, Witting et al [6] attempted to analyze unchanged quercetin, but were only able to detect quercetin conjugates while Mullen et al [7] reported trace levels of unchanged quercetin in one subject.…”
Section: Introductionmentioning
confidence: 97%
“…A lower detection limit of 1.5 pg (recalculated as 15 mg/mL of sample) was reached with electrochemical detection using the redox properties of the phenolic compounds [24]. Figure 2 shows a chromatogram of blood plasma from volunteers who drank green tea after enzymatic hydrolysis of glucuronides and quercetin sulfates.…”
Section: Analytical Methods For Biological Samples From Pk Studies Ofmentioning
confidence: 99%
“…Electrochemical detection has also been applied to biological samples, as described by Jin et al The aim of the study was to validate and apply a method for the quantification of quercetin in human plasma after the ingestion of a commercial canned green tea (Jin et al, 2004). The analysis was performed by an HPLC system coupled with electrochemical detection.…”
Section: Electrochemical Detectionmentioning
confidence: 99%